Fungal ethnoecology: observed habitat preferences and the perception of changes in fungal abundance by mushroom collectors in Poland - Marcin Andrzej Kotowski; Zsolt Molnár; Łukasz Łuczaj (BMC, 2021)
Abstract Background Scientists frequently raise the topic of data deficiency related to the abundance and distribution of macrofungi in the context of climate change. Our study is the first detailed documentation on locals' perception of fungal ecology which covers a large mycophilous region of Europe (Mazovia, Poland). Methods A total of 695 semi-structured interviews were carried out among local informants in 38 localities proportionally distributed throughout the study area (one locality approximately every 30 km). Interview questions concerned fungi species collected, their perceived habitats, and whether any changes had been noted in their abundance. As many as 556 respondents provided information concerning fungal ecology. In these descriptions, 35 taxa were mentioned by at least 5 respondents. Results The data collected during interviews allowed us to create collective folk descriptions of habitat preferences and a list of 98 different macro-, meso-, and microhabitats of macrofungi described by the respondents. This list of recurring habitats assigned to particular macrofungal taxa coincides with, and sometimes exceeds, data available in scientific publications. Some habitat preferences observed by the informants have not yet been researched or tested by science. Out of 695 respondents, 366 (53%) noticed a steady decrease in local macrofungi abundance, and only one person claimed to have observed a steady increase. Imleria badia was the only species with increased abundance, as noted by fifteen independent respondents. The main listed reason for abundance decrease was drought (f = 186). Conclusions Collected information on the ecology of fungi shows that local knowledge does not generally diverge from scientific knowledge. The acquired information related to macrofungal abundance and ecology may also be used as a tool for the formulation of new scientific questions and theories. The analysis of local fungi observations might contribute to broadening knowledge about local changes in fungi and enable new estimations related to large-scale analysis of macrofungal abundance.